If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -6)(x + -9) = (x + 9)(x + 1) Reorder the terms: (-6 + x)(x + -9) = (x + 9)(x + 1) Reorder the terms: (-6 + x)(-9 + x) = (x + 9)(x + 1) Multiply (-6 + x) * (-9 + x) (-6(-9 + x) + x(-9 + x)) = (x + 9)(x + 1) ((-9 * -6 + x * -6) + x(-9 + x)) = (x + 9)(x + 1) ((54 + -6x) + x(-9 + x)) = (x + 9)(x + 1) (54 + -6x + (-9 * x + x * x)) = (x + 9)(x + 1) (54 + -6x + (-9x + x2)) = (x + 9)(x + 1) Combine like terms: -6x + -9x = -15x (54 + -15x + x2) = (x + 9)(x + 1) Reorder the terms: 54 + -15x + x2 = (9 + x)(x + 1) Reorder the terms: 54 + -15x + x2 = (9 + x)(1 + x) Multiply (9 + x) * (1 + x) 54 + -15x + x2 = (9(1 + x) + x(1 + x)) 54 + -15x + x2 = ((1 * 9 + x * 9) + x(1 + x)) 54 + -15x + x2 = ((9 + 9x) + x(1 + x)) 54 + -15x + x2 = (9 + 9x + (1 * x + x * x)) 54 + -15x + x2 = (9 + 9x + (1x + x2)) Combine like terms: 9x + 1x = 10x 54 + -15x + x2 = (9 + 10x + x2) Add '-1x2' to each side of the equation. 54 + -15x + x2 + -1x2 = 9 + 10x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 54 + -15x + 0 = 9 + 10x + x2 + -1x2 54 + -15x = 9 + 10x + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 54 + -15x = 9 + 10x + 0 54 + -15x = 9 + 10x Solving 54 + -15x = 9 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 54 + -15x + -10x = 9 + 10x + -10x Combine like terms: -15x + -10x = -25x 54 + -25x = 9 + 10x + -10x Combine like terms: 10x + -10x = 0 54 + -25x = 9 + 0 54 + -25x = 9 Add '-54' to each side of the equation. 54 + -54 + -25x = 9 + -54 Combine like terms: 54 + -54 = 0 0 + -25x = 9 + -54 -25x = 9 + -54 Combine like terms: 9 + -54 = -45 -25x = -45 Divide each side by '-25'. x = 1.8 Simplifying x = 1.8
| 50-1/6=50 | | 4u+3u=9 | | 23+n=30 | | 7y+3y=1y+4y-10 | | 10(22+b)=500 | | -g+7.9=15.4 | | 15x(2)+10x=0 | | 10*x=25 | | 4x^2-24x+4y^2-28=0 | | (7x-27)+(4x+12)=180 | | 5x=12(x-11) | | n+58=62 | | x-3(1-7x)=2x+2 | | 5(2n+4)=9(4n+6)+2 | | (2x^2)+(3y^2)+6y-27=0 | | X^2-px+2p-3=0 | | -5=7t | | n^3=100 | | 7+3z-4=6z+4-2z | | e^10x=18e^3x | | 0.4x-5+6.1= | | 5h-9=-16b | | 7x+1-75=15x-75 | | n^2=1000 | | 5x+5x+5x+5x+5x+5=250 | | 3B+2.5=4 | | (x^3-3(x)y^2)dx+(y^3-3x^2(y))dy=0 | | 4(a-4)+4=2a-6 | | 3(y+11)-7=13 | | 10x-2x+18=2(4x+9) | | 4.5=-.5(x-7.1) | | 11/2-3/4= |